Coxsackievirus B3 infects and disrupts human induced-pluripotent stem cell derived brain-like endothelial cells - Mamana, Julia; Humber, Gabrielle M.; Espinal, Eric R.; Seo, Soojung; Vollmuth, Nadine; Sin, Jon; Kim, Brandon J. (Frontiers in Cellular and Infection Microbiology, 2023)
Coxsackievirus B3 (CVB3) is a significant human pathogen that is commonly found worldwide. CVB3 among other enteroviruses, are the leading causes of aseptic meningo-encephalitis which can be fatal especially in young children. How the virus gains access to the brain is poorly-understood, and the host-virus interactions that occur at the blood-brain barrier (BBB) is even less-characterized. The BBB is a highly specialized biological barrier consisting primarily of brain endothelial cells which possess unique barrier properties and facilitate the passage of nutrients into the brain while restricting access to toxins and pathogens including viruses. To determine the effects of CVB3 infection on the BBB, we utilized a model of human induced-pluripotent stem cell-derived brain-like endothelial cells (iBECs) to ascertain if CVB3 infection may alter barrier cell function and overall survival. In this study, we determined that these iBECs indeed are susceptible to CVB3 infection and release high titers of extracellular virus. We also determined that infected iBECs maintain high transendothelial electrical resistance (TEER) during early infection despite possessing high viral load. TEER progressively declines at later stages of infection. Interestingly, despite the high viral burden and TEER disruptions at later timepoints, infected iBEC monolayers remain intact, indicating a low degree of late-stage virally-mediated cell death, which may contribute to prolonged viral shedding. We had previously reported that CVB3 infections rely on the activation of transient receptor vanilloid potential 1 (TRPV1) and found that inhibiting TRPV1 activity with SB-366791 significantly limited CVB3 infection of HeLa cervical cancer cells. Similarly in this study, we observed that treating iBECs with SB-366791 significantly reduced CVB3 infection, which suggests that not only can this drug potentially limit viral entry into the brain, but also demonstrates that this infection model could be a valuable platform for testing antiviral treatments of neurotropic viruses. In all, our findings elucidate the unique effects of CVB3 infection on the BBB and shed light on potential mechanisms by which the virus can initiate infections in the brain.